Application of SWOT Analysis for Increased Secretarial Productivity - Ajani, Safurat Toyin; Folorunso, Oluwole Isaac; Shabi, Sururat Omobolanle (NIU Journal of Educational Research, 2025)
This work on Application of SWOT Analysis for increased Secretarial Productivity was approached from professional, rather than academic angle.  The purpose was to highlight how honestly conducted SWOT analysis can increase productivity of secretarial staff in any organization.  Relevant literature, personal experience and observation methods were adopted and various concepts in the topic reviewed.  The article X-rayed the contents of each letter in SWOT and their effects on productivity of secretarial professionals.  It was revealed that the strengths of secretarial profession lie on its indispensability in any organization, among others.  Many weaknesses, like poor mindset, low esteem and inferior complex mostly generated by the practitioners and opportunities to improve the general outlook and efficiency of the practitioners abound in the external environment of secretarial practitioners were identified.   Threats to the profession include: economic, technology and environment, among many others. It was concluded that to advance secretarial profession to a new pinnacle in Nigeria secretaries are to individually conduct honest and regular personal SWOT analysis.  Secretaries must continually up-scale their strength, identify   areas of their weakness and take proactive measures. They should leverage on technology in addition to other numerous readily opportunities in the profession as well undertake appropriate actions to mitigate the effects of threats as they unfold.  Keywords: Strengths, weaknesses, opportunities, threats.